Calcium-Dependent Regulation of Desmosomal Proteins in Human Meibomian Gland Epithelial Cells - Garreis, Fabian; Adelung, Susanne; Schicht, Martin; Hampel, Ulrike; Paulsen, Friedrich (Investigative Ophthalmology & Visual Science, 2025)
PURPOSE. Meibomian gland dysfunction (MGD) is the leading cause of dry eye disease and is characterized by altered function of the meibomian glands. These glands produce lipids that form the outer layer of the tear film, which is critical for reducing evaporation from the ocular surface. Desmosomes—adhesive intercellular junctions—have been implicated in the differentiation processes of meibocytes, but their precise role remains to be further elucidated. This study aimed to get further insights into the function of desmosomal components in meibocyte differentiation and to improve our understanding of the pathogenesis of MGD. METHODS. Immunohistochemical and immunofluorescence analyses of C57BL/6 mouse eyelid sections were performed to observe distribution patterns of desmosomal proteins in meibomian glands. Stimulation experiments using an immortalized human meibomian gland epithelial cell (HMGEC) line subjected to high calcium and fetal calf serum conditions, followed by real-time RT-PCR and Western blot analysis were performed to assess gene and protein expression of desmosomal components. Immunofluorescence was used to determine the intracellular localization within HMGEC. RESULTS. Our results indicate that a high calcium concentration promotes cell membrane localization and significantly increases the expression of desmocollin 3, desmoglein 2, and desmoplakin 1/2 in serum-free cultured HMGEC. Immunohistochemistry in C57BL/6 mice shows that desmosomal proteins are present at all stages of differentiation. Desmocollin and desmoglein are prevalent in basal and differentiating cells, whereas desmoplakin is distributed evenly, except in hypermature cells. CONCLUSIONS. Our study demonstrates the impact of calcium concentration on the expression and localization of desmosomal proteins and their role in meibocyte differentiation in both human and mouse models. To further understand the physiological mechanisms of desmosomes in the meibomian gland and the pathophysiology of MGD, further research into desmosomal functionality is required, which may pave the way for novel therapeutic strategies for evaporative dry eye disease.
CRIS-Team Scopus Importer:2025-07-04
Keywords: desmosomes; dry eye disease (DED); meibocyte differentiation; meibomian gland dysfunction (MGD); tear film stability